2014
DOI: 10.1158/1078-0432.ccr-12-3909
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic Interaction between the HDAC Inhibitor, MPT0E028, and Sorafenib in Liver Cancer Cells In Vitro and In Vivo

Abstract: Purpose To investigate the antitumor activities of a histone deacetylase (HDAC) inhibitor, MPT0E028, plus sorafenib in liver cancer cells in vitro and in vivo. Experimental Design Different liver cancer cell lines were exposed to sorafenib in the presence or absence of MPT0E028, and cell viability was determined by MTT assay. Effects of combined treatment on cell cycle and intracellular signaling pathways were assessed by flow cytometry and Western blot analysis. The Hep3B xenograft model was used to examine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 50 publications
5
30
0
1
Order By: Relevance
“…Its antitumor activities include inducing apoptosis, HDAC activity inhibition, Akt pathway deactivation, and regulation of many genes in vitro ; and prolongation of survival rate and reduction of tumor volume in vivo . Our previous work [12-14] and current studies suggest that MPT0E028 has greater efficacy in vivo and in vitro compared to SAHA. In totality, our results provide compelling evidence that MPT0E028 can be an effective antitumor agent in the treatment of B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Its antitumor activities include inducing apoptosis, HDAC activity inhibition, Akt pathway deactivation, and regulation of many genes in vitro ; and prolongation of survival rate and reduction of tumor volume in vivo . Our previous work [12-14] and current studies suggest that MPT0E028 has greater efficacy in vivo and in vitro compared to SAHA. In totality, our results provide compelling evidence that MPT0E028 can be an effective antitumor agent in the treatment of B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, combinations with classical chemotherapeutic agents [43, 44] or new small molecule inhibitors [45] are being investigated. According to our previous study, MPT0E028 also showed synergism in combination with tyrosine kinase inhibitors, such as erlotinib and sorafenib, in non-small cell lung cancer (NSCLC) and liver cancer, respectively [13, 14]. Therefore, combination treatment with different therapeutic agents in solid tumors may broaden the potential usage of MPT0E028.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies have demonstrated antiproliferative, antiangiogenic, and proapoptotic effects from combining HDAC inhibitors with sorafenib in epithelial tumor cells,1921 including HCC cells 22. Several phase I studies investigated HDAC inhibitors in combination with sorafenib, and these studies either support future clinical development of an entinostat/sorafenib combination in patients with advanced solid tumors43 or show that the combined sorafenib and vorinostat treatment was not tolerated and had no confirmed response in patients with renal cell carcinoma and NSCLC 44.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of HCC patients do not respond to sorafenib, and most, if not all, patients who initially respond to sorafenib develop tumor resistance after a few months of treatment 18. Preclinical studies have also shown that combining HDAC inhibitors with sorafenib can have antiproliferative, antiangiogenic, and proapoptotic effects on epithelial tumor cells including HCC cells 1922…”
Section: Introductionmentioning
confidence: 99%